In situ TEM studies of micron-sized all-solid-state fluoride ion batteries: Preparation, prospects, and challenges - Anji Munnangi (Microscopy Research and Technique, 2016)
Trustworthy preparation and contacting of micron‐sized batteries is an essential task to enable reliable in situ TEM studies during electrochemical biasing. Some of the challenges and solutions for the preparation of all‐solid‐state batteries for in situ TEM electrochemical studies are discussed using an optimized focused ion beam (FIB) approach. In particular redeposition, resistivity, porosity of the electrodes/electrolyte and leakage current are addressed. Overcoming these challenges, an all‐solid‐state fluoride ion battery has been prepared as a model system for in situ TEM electrochemical biasing studies and first results on a Bi/La0.9Ba0.1F2.9 half‐cell are presented.